2017
DOI: 10.1093/mnras/stx782
|View full text |Cite
|
Sign up to set email alerts
|

Gran Telescopio Canarias observations of an overdense region of Lyman α emitters at z = 6.5

Abstract: We present the results of our search for the faint galaxies near the end of the Reionisation Epoch. This has been done using very deep OSIRIS images obtained at the Gran Telescopio Canarias (GTC). Our observations focus around two close, massive Lyman Alpha Emitters (LAEs) at redshift 6.5, discovered in the SXDS field within a large-scale overdense region (Ouchi et al. 2010). The total GTC observing time in three medium band filters (F883w35, F913w25 and F941w33) is over 34 hours covering 7.0 × 8.5 arcmin 2 (o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 108 publications
(140 reference statements)
6
31
1
Order By: Relevance
“…Here we define overdensities as regions whose overdensity significances are higher than 4σ levels. We identify overdensities previously reported in Higuchi et al (2018); z6PCC1, z6PCC3, and z6PCC4 at z = 5.7, and z7PCC24 and z7PCC26 (see also Chanchaiworawit et al 2017Chanchaiworawit et al , 2019 at z = 6.6. 1 z6PCC1 is the same structures reported in Ouchi et al (2005) and Jiang et al (2018, see Section 4.1).…”
Section: Lae Samplesupporting
confidence: 75%
“…Here we define overdensities as regions whose overdensity significances are higher than 4σ levels. We identify overdensities previously reported in Higuchi et al (2018); z6PCC1, z6PCC3, and z6PCC4 at z = 5.7, and z7PCC24 and z7PCC26 (see also Chanchaiworawit et al 2017Chanchaiworawit et al , 2019 at z = 6.6. 1 z6PCC1 is the same structures reported in Ouchi et al (2005) and Jiang et al (2018, see Section 4.1).…”
Section: Lae Samplesupporting
confidence: 75%
“…Deriving the Lyα rest-frame equivalent widths of the LAEs could be just a simple task, if any continuum flux would have been detected. However, in our case, the UV continuum was not detected, beyond 2σ level, for any of the LAEs, not even in the photometric observations, except for 3 objects (Chanchaiworawit et al 2017). Thus, the only sound solution to estimate the rest-frame equivalent widths of the LAEs is to give lower limit values.…”
Section: Lyα Equivalent Widths and Escape Fractionscontrasting
confidence: 64%
“…We have confirmed 10 out of the 16 LAE candidates, which is a success rate of 62.5% or non detection rate of 37.2%. This percentage is slightly above 1 3 , which is the spuriousness rate previously determined in the photometry (Chanchaiworawit et al 2017).…”
Section: The Final Spectrasupporting
confidence: 48%
“…We used a 0 ′′ .8 slit width that gives a spectral resolution of 1, 000 − 2, 000. We perform data reduction with the Carnegie Observatories System for MultiObject Spectroscopy (COSMOS) pipeline, and detect Lyα emission lines around 8160Å (9210Å ) for 130 (22) Ouchi et al 2010, and Hu et al 2016, we use the redshift catalogs for the spectroscopically confirmed LAEs at z = 5.7 (6.6) taken from Ouchi et al (2005), Ouchi et al (2008), Mallery et al (2012), Chanchaiworawit et al (2017), and Guzmán et al (in preparation). We make unified spectroscopic catalogs of LAEs at z = 5.7 and 6.6 Tables 4 and 5, respectively.…”
Section: Magellan/imacs Observationmentioning
confidence: 99%